Characterisation of new gated optical image intensifiers for fluorescence lifetime imaging - Sparks,H; Gorlitz,F; Kelly,D; Warren,SC; Kellet,PA; Garcia,E; Dymoke-Bradshaw,AKL; Hares,JD; Neil,MAA; Dunsby,C; French,PMW (Review of Scientific Instruments, 2017)
We report the characterisation of gated optical image intensifiers for fluorescence lifetime imaging (FLIM), evaluating the performance of several different prototypes that culminate in a new design that provides improved spatial resolution conferred by the addition of a magnetic field to reduce the lateral spread of photoelectrons on their path between the photocathode and microchannel plate, and higher signal to noise ratio conferred by longer time gates. We also present a methodology to compare thesesystems and their capabilities, including the quantitative readouts of Förster resonant energy transfer (FRET).